Medicines based on coordination compounds of iron and other microelements for the treatment of anemia (The Peerian Journal, 2024)
Today, the Republic pays special attention to the production of chemical industry products and their implementation in the economic sectors. Based on the development strategy of the Republic of Uzbekistan, aimed at "further modernization and diversification of industry by transferring it to a qualitatively new level, aimed at the accelerated development of high-tech manufacturing industries, primarily in the production of finished products with high added value based on deep processing of local raw materials", "development of the production of fundamentally new types of products and technologies" the most important tasks are defined. In this aspect, the development of leading sectors of the national economy, including the chemical industry, obtaining new ligands based on a given organic synthesis and the use of complex compounds of d-metals based on them, is an urgent task.